Visualizing RNA Structures by SAXS-Driven MD Simulations - He, Weiwei; Henning-Knechtel, Anja; Kirmizialtin, Serdal (Frontiers in Bioinformatics, 2022)
The biological role of biomolecules is intimately linked to their structural dynamics. Experimental or computational alone techniques are often insufficient to determine accurate structural ensembles. We use all-atom MD simulations and couple it to Small-Angle X-ray Scattering (SAXS) experiments to resolve the structural dynamics of RNA molecules. To accomplish our task we use a set of re-weighting and biasing techniques tailored to RNA molecules. To showcase the approach, we study two RNA molecules; a riboswitch that shows structural variations upon ligand binding, and a two-way junction RNA that shows structural heterogeneity and high sensitivity to salt conditions. Integration of MD simulations and experiments allows accurate construction of conformational ensembles of RNA molecules. We observe a dynamic change of the SAM-I riboswitch conformations depending on its binding partners. The binding of SAM and Mg2+ cations stabilize the compact state. The absence of Mg2+ or SAM leads to the loss of tertiary contacts, resulting in a dramatic expansion of the riboswitch conformations. The sensitivity of RNA structures to ionic strength demonstrates itself in the helix junction helix (HJH). Our approach allows visualizing the RNA conformational ensemble in varying salt conditions. The HJH shows non-monotonic compaction as the ionic strength increase. The physics-based picture derived from MD simulations allows biophysical characterization of RNA molecules. All in all, experimentally guided MD simulations offer great prospects into studying RNA structural dynamics.